The Potential Of Avocado Seed Extract (Persea Americana) In Inhibiting The Release Of Metal Ions In Cuniti And Stainless Steel Based Orthodont Wire - Herniyati; Leliana Sandra Devi; Dwi Prijatmoko; Rudy Joelijanto; Swasthi Prasetyarini; FX Ady Soesetijo; Rina Sutjiati; Aura Sekar Asmarani Subagyo; Erlangga Bayu Mustika Aji (International Journal of Health and Pharmaceutical (IJHP), 2024)
The release of ions is the initial stage of the corrosion process in an orthodontic wire. Continuous release of ions can reduce the effectiveness and performance of the orthodontic wire. Continuous release of ions in CuNiTi orthodontic wire can change the properties of the wire and trigger hypersensitivity reactions, also in stainless steel orthodontic wire which experiences continuous release of ions can reduce its stiffness. The tannin in avocado seeds is useful as a corrosion inhibitor it can inhibit the release of ions because they are able to bind with metal ions and form a passive layer also able to bind with Fe ions in stainless steel orthodontic wires to form a passive surface layer which is able to inhibit the release of ions when the corrosion process occurs. The aim of this research is to determine the effect of avocado seed extract as a corrosion inhibitor on the release of metal ions from CuNiTi and stainless steel orthodontic wires. Rectangular CuNiTi and stainless steel orthodontic wires measuring 0.017 x 0.025 inches were taken in 3 groups (1 control group soaked in artificial saliva and 2 treatment groups soaked in avocado seed extract). The samples were soaked in avocado seed extract with a concentration of 1.5 g/L and 2 g/L for 7 days. To see the release of ions, an X-Ray Fluorescence test is carried out. In CuNiTi orthodontic wire from the one way ANOVA test showed that there was a significant difference between the control group and all treatment groups on Cu, Ni and Ti ions. The Post Hoc LSD test showed that there were significant differences between the control group, treatment group 1 and treatment group 2 in Cu, Ni and Ti ions with a p value. In stainless steel orthodontic wire, the one way ANOVA test showed that there was a significant difference between the control group and all treatment groups in Fe and Ni ions but not significant in Cr ions in the ion release test with a p value <0.05. The Post Hoc LSD test showed that there were significant differences between the control group, treatment group 1 and treatment group 2 in Fe and Ni ions with a p value <0.05. Providing avocado seed extract with tannin content at concentrations of 1.5 g/L and 2 g/L can inhibit the rate of ion release in CuNiTi and stainless steel orthodontic wires due to the corrosion process.